Effect of the knee-chest position on cerebral blood flow in patients undergoing lumbar spinal surgery. Issue 11 (November 1989) - Pittet, J F; Ramadan, A; Morel, D R; Forster, A
Abstract : The cerebral haemodynamic effect of the knee-chest position was evaluated in 15 anaesthetised patients undergoing elective lumbar disc surgery and divided into a control group (n = 8) where cerebral blood flow (CBF) was measured twice in the supine position and an experimental group (n = 7) where the first CBF was measured in the supine position and the second in the knee-chest position. CBF was measured by a modified intravenous 133xenon washout technique. Mean global CBF did not change in control group (56.1, SD 9.2 versus 52.8, SD 10.8 units) and was not significantly modified by the knee-chest posture, 51.8, SD 8.8 units versus 53.9, SD 7.4 units in the supine position. The results indicate that mean global CBF in the knee-chest position is not different from CBF in the supine position in healthy patients.